Effects of probiotic VSL#3 and synbiotic VSL#3 associated with yacon- based product (PBY) on gut microbiota and on the development of intestinal diseases in mice - Cruz, Bruna Cristina dos Santos (2022)
Intestinal diseases, including colorectal cancer (CRC) and inflammatory bowel diseases (IBD) have high prevalence and mortality rates worldwide. Although there is a genetic component associated with the etiology of these diseases, the participation of environmental and lifestyle-related factors in their development has been increasingly demonstrated. Changes in the composition and activity of the intestinal microbiota, which may be associated, for example, with inadequate feeding, seem to contribute to the increased risk of development of both CRC and IBD. Thus, it is increasing and justifiable the search for food or no-food compounds, that can reestablish the balance of the microbiota and modify the intestinal microenvironment, reducing the risk of diseases. The use of probiotics and prebiotics, isolated or combined (synbiotic), is one of the main strategies for targeted modulation of the microbiota, either by adding specific microorganisms or by conferring a selective advantage on resident microorganisms. The general objective of this study was to investigate the effects of probiotic VSL#3 and synbiotic VSL#3 associated with yacon- based product (PBY), on the modulation of the gut microbiota and its influence on the development of precursor lesions of CRC and on the manifestations of colitis- associated carcinogenesis (CAC). For this, two distinct experiments were conducted: in Experiment 1, wild C57BL6/J mice received, for 13 consecutive weeks, the probiotic multispecies VSL#3 isolated (probiotic group - PRO) or associated with PBY (synbiotic group - SYN) and were induced to colorectal carcinogenesis with 1,2- dimethylhydrazine (DMH). In Experiment 2, knockout mice for interleukin-10 (IL-10 -/- ), a spontaneous colitis model, were induced to carcinogenesis with DMH and received the synbiotic VSL#3 + PBY for the same period. In Manuscript 1 (Published) (Experiment 1), our aim was to evaluate the effects of probiotic and synbiotic on the composition of the intestinal microbiota and their influence on the development of precursor lesions of CRC. It was observed that both the use of probiotic and synbioticmodified the composition of the microbiota; changes in the microbiota of the control group were also observed, confirming that carcinogenesis itself alters the resident microbial community. The precursor lesions of CRC were significantly reduced in the SYN group, but not in the PROCiência da Nutrição group. This outcome is possibly associated with changes in the intestinal microenvironment induced by microbiota modulation in the SYN group, such as significant reduction of inflammatory response in the colon, reduction of the activity of the pro-carcinogenic enzyme -glucuronidase, and increase in short-chain fatty acids (SCFA). Manuscript 2 (Published) (Experiment 1) sought to investigate possible mechanisms of action associated or that could explain the results obtained in Article 1. Thus, the effects of probiotic and synbiotic on oxidative stress and intestinal permeability were investigated. Probiotic and synbiotic have antioxidant activity in vitro. Both PRO and SYN groups had lower concentrations of oxidation products, manlondialdehyde and protein carbonyl, compared to the control group. The activity of the antioxidant enzyme catalase was higher in the SYN group compared to the others. It was also observed an increase in the depth crypts in the PRO and SYN groups, which corroborates the reduction in intestinal permeability (measured by urinary lactulose excretion) in these groups. Manuscript 3 (Submitted) (Experiment 1) evaluated the effect of probiotic and synbiotic on the functional metabolic pathways of the microbiota and on the expression of genes associated with colorectal carcinogenesis. The SYN group showed a highly differentiated intestinal community based on the MetaCyc pathways. Of the 351 predicted functional pathways, 222 differed between groups. Most of them were enriched in the SYN group, namely: amino acid biosynthesis pathways, small molecule biosynthesis pathways, carbohydrate degradation pathways, and fermentation pathways. In addition, synbiotic was able to stimulate the anti-inflammatory immune response and reduce gene expression of PCNA and c-myc. As demonstrated in these studies, the use of the synbiotic VSL#3 + PBY significantly reduced the incidence of precursor lesions of CRC and down- regulated the expression of genes associated with carcinogenesis. We believe that these findings are the result of the synbiotic influence on the composition and activity of the intestinal microbiota, notably through reduced inflammatory response, improved oxidative stress, reduced pro-carcinogenic enzyme activity, increased SCFA and reduced permeability intestinal. Manuscript 4 (Published) (Experiment 2) aimed to evaluate the effect of the synbiotic VSL#3 + PBY in a colitis-associated carcinogenesis (CAC) model. Preservation of intestinal architecture, increased activity of antioxidantenzymes superoxide dismutase and catalase, and AGCC concentrations, especially butyrate, were observed. Regarding the composition of the intestinal microbiota, we highlight that the microbiota of the experimental model used was characterized by a restricted biodiversity, with a limited number of bacterial genera representing the total microbial community. This finding has been consistently demonstrated in cases of cancer in experimental models and in humans, and in IBD patients. In Manuscript 5 (Submission process) (Experiment 2), we investigate the effects of the synbiotic VSL#3 and PBY on the intestinal inflammatory response, expression of genes associated with colorectal carcinogenesis, β-glucuronidase enzyme activity, functional metabolic pathways of the microbiota, and production of fecal fatty acids. Lower expression of p53 and c-myc in the synbiotic group compared to control group was observed. Similarly, IL-17 levels were also lower. There was also an increase in IL-4 in the synbiotic group compared to negative control. The principal component analysis revealed a poorly differentiated intestinal community based on MetaCyc pathways. These findings support the similarity in predicted metabolic pathways between groups. There was also a reduction in the activity of the -glucuronidase enzyme and an increase in short-chain fatty acids in the synbiotic group. Thus, it is suggested that the synbiotic could be a novel potential health-protective natural agent against CAC. Keywords: Colorectal cancer. Inflammatory bowel disease. Gut microbiota. Probiotic. Prebiotic. Synbiotic.